The Role of Digital Citizenship Education in Building Responsible Online Behavior and Preventing Cyberbullying among Adolescents - Dedi Gunawan Saputra; Arjulayana; Cristy A. Dacara (International Journal of Educational Technology and Society, 2024)
This research explores the impact of digital citizenship education (DCE) in promoting responsible online behavior and reducing cyberbullying among adolescents. With the increasing prevalence of online risks such as cyberbullying, online aggression, and privacy breaches, this study focuses on understanding how structured DCE curricula can equip adolescents with the necessary knowledge and skills to navigate the digital world responsibly. The research aims to assess the effectiveness of a curriculum-based intervention delivered over 8 weeks, involving pre- and post-assessments to measure changes in students' knowledge, attitudes, and online behaviors. Data was collected through surveys, behavioral assessments, and interviews to evaluate the impact of the curriculum on students’ online conduct. The findings reveal a significant reduction in harmful online behaviors, including cyberbullying, and a marked improvement in empathy, respect, and online responsibility. The study demonstrates that proactive educational approaches, such as DCE, are more effective than punitive measures in fostering long-term positive online behaviors. The conclusion emphasizes the need for integrating DCE into school curricula, with recommendations for educators, policymakers, and parents to reinforce digital citizenship principles both in the classroom and at home.